The proqol-21: A revised version of the professional quality of life (ProQOL) scale based on Rasch analysis - Heritage, B.; Rees, Clare; Hegney, D. (Public Library of Science, 2018)
The Professional Quality of Life scale is a measure intended to provide practitioners and researchers with an indication of a caring professional’s compassion satisfaction, burnout, and secondary traumatic stress. While this measure has been used extensively in nursing research, owing to the relevancy of patient-care associated satisfaction and fatigue within this profession, information regarding the construct validity of this measure is less well represented in the literature. We examined the construct validity of the Professional Quality of Life scale using a Rasch analysis procedure on each of its three scales, as a means of substantiating their measurement adequacy. Responses on the Professional Quality of Life scale from 1615 registered nurses (age x̅ = 46.48 years, SD = 11.78) were analysed. While support for the measurement adequacy (invariance, person/item fit, and unidimensionality) of the compassion satisfaction scale was found, the burnout and secondary traumatic stress scales did not demonstrate adequate measurement properties. We instead present an alternative measurement model of these subscales, involving items from each, to form a robust measure of compassion fatigue, and provide recoding, scoring, and normed scores for both measures. Our findings indicate that use of the Professional Quality of Life scale’s burnout and secondary traumatic stress scales may require caution, while our revised compassion satisfaction and fatigue scales provide robust measurement options for practitioners and researchers.